CONSUMER BUYING BEHAVIOR TOWARDS HERBAL-BASED PRODUCTS IN MALAYSIA - Juwaidah Sharifuddin; Nurliyana Ahmad Mazlan; Golnaz Rezai (UNEJ e-Proceeding, 2012)
Remarkable growth in the use of herbal-based products has recently been noted. InMalaysia, herbal-based product consumption has gained increasing attention by consumersover the past several years. A variety of factors may influence this increasing trend ofconsumption including changes in lifestyle and belief in natural product. The aim of thispaper is to identify the factors influencing the usage of herbal-based products. Data fromfour hundred and fifty respondents was collected by means of self-administeredquestionnaire, using the snowballing method. The findings revealed that 57.8% of totalsubjects have experience in buying herbal-based products. Research indicates that there aresignificant differences based on gender, education level and age on the use of herbal-basedproducts. Other than the attribute and quality of products, the consumption of herbal-based products are also influenced by both lifestyle and personality of the consumers. With the growing demand of herbal-based product, Malaysians government as well as the industryplayers has to increase their effort in terms of research and consumer education withrespect to herbal-based products. The results of this study will hopefully enlighten themarketers of herbal-based products and help them in devising appropriate marketingstrategies in targeting consumers in Malaysia.